Embryogenesis plasticity and the transmission of maternal effects in Daphnia pulex. Issue 5 (24th June 2020) - Hasoon, Megan S. R.; Plaistow, Stewart J.
Abstract: Understanding how genetic, nongenetic, and environmental cues are integrated during development may be critical in understanding if, and how, organisms will respond to rapid environmental change. Normally, only post‐embryonic studies are possible. But in this study, we developed a real‐time, high‐throughput confocal microscope assay that allowed us to link Daphnia embryogenesis to offspring life history variation at the individual level. Our assay identified eight clear developmental phenotypes linked by seven developmental stages, the duration of which were correlated with the expression of specific offspring life history traits. Daphnia embryogenesis varied not only between clones reared in the same environment, but also within a single clone when mothers were of different ages or reared in different food environments. Our results support the hypothesis that Daphnia embryogenesis is plastic and can be altered by changes in maternal state or maternal environment. As well as furthering our understanding of the mechanisms underpinning parental effects, our assay may also have an industrial application if it can be used as a rapid ecotoxicological prescreen for testing the effect that pollutant doses have on offspring life histories traditionally assayed with a 21‐day Daphnia reproduction test. Abstract : In this study we link maternal environments to embryogenesis and life history variation to test the hypothesis that Daphnia embryogenesis is plastic and can be altered by changes in maternal state or environment. We find that patterns of embryogenesis vary across clones within the same environment, but also within a single clone when mothers experienced different food environments or were different ages Research Highlights: We use a confocal microscope assay to demonstrate that embryogenesis varies not only between Daphnia clones, but also within a clone when mothers are of different ages or they have experienced different food environments.